Rationalisation of Establishment Cost in the Eucalyptus Plantations of Kerala - Nair, N. R. (Indian Forester, 1975)
This paper deals with an attempt at Rationalising the cost of establishment of Eucalyptus plantations in Kerala, by the application of Work Study techniques. As a result of this, a savings of 66.5% in expenditure could be indicated and effected. Besides, detailed job specifications for the different jobs were also formulated, which among other things, will help to stabilize the grounds for negotiating wages and fixing rates for works. These proposals have been implemented in Kerala State from 1971 onwards.